GEOCHEMICAL AND PETROLOGICAL STUDIES OF A CARBONATISED METALAMPROPHYRE AT KALAGALLA -: EVIDENCE FOR SHOSHONITIC CALC-ALKALINE MAGMATISM WITHIN AURIFEROUS RAMAGIRI-PENAKACHERLA SCHIST BELT (2.5 Ga), EASTERN DHARWAR CRATON, SOUTHERN INDIA - Pothuri, Rameshchandra Phani; Lira, Raúl; Espeche, María José; Rokalla, Ananda Reddy (Geochimica Brasiliensis, 2020)
Geochemical and petrological characteristics of a lamprophyre dyke at Kalagalla intruded into the auriferous schistose rocks of the Ramagiri-Penakacherla Schist Belt, Anantapur district, Andhra Pradesh, India are presented here. The Kalagalla lamprophyre (KGL) is a melanocratic rock exhibiting typical knobbly or pustular texture on the rock surface. The micro-textures and mineralogy typical of lamprophyres are obscured by metamorphism; however, it exhibits porphyritic, nemato-granoblastic texture representating greenschist facies metamorphism. The rock is sheared and carbonatised possessing several globules formed by polycrystalline aggregates of calcite rimmed by coronitic subhedral plagioclase and biotite-phlogopite, evidencing its magmatic origin. The mineral assemblages noticed in thin-sections include amphibole, plagioclase, biotite-phlogopite with calcite ocelli as essential while apatite, zircon, magnetite, ilmenite and several opaque minerals as accessory phases. The SEM-EDS investigation on the opaque minerals revealed accessory sulphide and silicate phases like As-free pyrite, haematitised Ni-bearing chalcopyrite and Ni-As-Co- minerals indicative of sulphidation associated with greenstonevauriferous lodes; along with oxide phases like LREE-bearing titanite partially transformed into leucoxene and goethite. Presence of amphibole and dominance of plagioclase, it is presumably a spessartite variety. Based on its geochemistry, the rock is classified as a shoshonitic calc-alkaline lamprophyre. The LREE-bearing titanite appears to be the contributor of LREE enrichment. The high Mg# (77-79), Ni (153-162 ppm) and Cr (380-470 ppm) support a mantle source. The trace and REE patterns (ƩREE:326-343 ppm, LREE>HREE) indicate ivolvement of residual garnet at the source enriched in phlogopite in a ‘subduction-related’ environment. The absence of Eu anomaly reflects lack of plagioclase fractionation. The high Zr/Hf ratio (163-202) indicates carbonatite metasomatism and lack of crustal contamination. Further investigations are in progress.